An investigation of the validity of the Work Assessment Triage Tool clinical decision support tool for selecting optimal rehabilitation interventions for workers with musculoskeletal injuries. (March 2016) - Qin, Ziling; Armijo-Olivo, Susan; Woodhouse, Linda J; Gross, Douglas P
Objective: To evaluate the concurrent validity of a clinical decision support tool (Work Assessment Triage Tool (WATT)) developed to select rehabilitation treatments for injured workers with musculoskeletal conditions. Design: Methodological study with cross-sectional and prospective components. Setting: Data were obtained from the Workers' Compensation Board of Alberta rehabilitation facility in Edmonton, Canada. Subjects: A total of 432 workers' compensation claimants evaluated between November 2011 and June 2012. Main measures: Percentage agreement between the Work Assessment Triage Tool and clinician recommendations was used to determine concurrent validity. In claimants returning to work, frequencies of matching were calculated and compared between clinician and Work Assessment Triage Tool recommendations and the actual programs undertaken by claimants. The frequency of each intervention recommended by clinicians, Work Assessment Triage Tool, and case managers were also calculated and compared. Results: Percentage agreement between clinician and Work Assessment Triage Tool recommendations was poor (19%) to moderate (46%) and Kappa = 0.37 (95% CI −0.02, 0.76). The Work Assessment Triage Tool did not improve upon clinician recommendations as only 14 out of 31 claimants returning to work had programs that contradicted clinician recommendations, but were consistent with Work Assessment Triage Tool recommendations. Clinicians and case managers were inclined to recommend functional restoration, physical therapy, or no rehabilitation while the Work Assessment Triage Tool recommended additional evidence-based interventions, such as workplace-based interventions. Conclusions: Our findings do not provide evidence of concurrent validity for the Work Assessment Triage Tool compared with clinician recommendations. Based on these results, we cannot recommend further implementation of the Work Assessment Triage Tool. However, the Work Assessment Triage Tool appeared more likely than clinicians to recommend interventions supported by evidence; thus warranting further research.